2000
DOI: 10.1159/000052653
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Voice Onset Time in Dysarthric Patients: Methodological Considerations

Abstract: Voice onset time (VOT) reflects the timing control between laryngeal and supralaryngeal adjustments. It has been studied both in normal speakers and patients with speech disorders, but very little information has been published on the feasibility of this measure in clinical practice. We examined 10 repeated utterances involving the voiceless stop consonants [p], [t] and [k] in 110 subjects (27 controls, 48 with spastic dysarthria and 35 with hypokinetic dysarthria). The mean rate of measurable VOT was 95% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
(40 reference statements)
0
17
0
2
Order By: Relevance
“…This can either be due to the impossibility to determine the location of the burst or the onset of regular striations on the spectrogram [7]. The burst does not occur when a subject fails to achieve full closure in the production of stop constants.…”
Section: Discussionmentioning
confidence: 99%
“…This can either be due to the impossibility to determine the location of the burst or the onset of regular striations on the spectrogram [7]. The burst does not occur when a subject fails to achieve full closure in the production of stop constants.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of burst onset and the end of the vocalic nucleus are generally straightforward. When double bursts occurred, the first burst was defined as the onset of burst [37][38][39] . The same criterion was used in the case of multiple bursts.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Thus, the VOT measure itself has not provided conclusive results concerning the super- and supra-laryngeal control and coordination in PD patients due to the difficulty involved in making the acoustic measurements. However, it has been argued by Özsancak et al [25] that a more simple judgment of whether a VOT measurement could be made or not may provide a more suitable quantification of this aspect of speech production in dysarthric patients [25]. Özsancak et al [25] argued that the relative frequency of which VOT measurements are afforded by the produced plosives correlates with the articulatory control and precision in the patient: a positive speech outcome in the disease is argued to lead to an increase in percent measurable VOT.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been argued by Özsancak et al [25] that a more simple judgment of whether a VOT measurement could be made or not may provide a more suitable quantification of this aspect of speech production in dysarthric patients [25]. Özsancak et al [25] argued that the relative frequency of which VOT measurements are afforded by the produced plosives correlates with the articulatory control and precision in the patient: a positive speech outcome in the disease is argued to lead to an increase in percent measurable VOT. In addition, Özsancak et al [25] found positive correlation between measurability of VOT and Intelligibility Scores in dysarthric patients.…”
Section: Introductionmentioning
confidence: 99%